Frontocingulate Dysfunction Is Associated with Depression and Decreased Serum PON1 in Methamphetamine-Dependent Patients - Ghavidel N (Dove Medical Press, 2020)
Nooshin Ghavidel,1 Fariba Khodagholi,1 Abolhassan Ahmadiani,1 Reza Khosrowabadi,2 Sareh Asadi,3 Jamal Shams4 1Neuroscience Research Center, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 2Institute for Cognitive and Brain Sciences, Shahid Beheshti University, Tehran, Iran; 3NeuroBiology Research Center, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 4Behavioral Research Center, Shahid Beheshti University of Medical Sciences, Tehran, IranCorrespondence: Sareh AsadiNeuroBiology Research Center, Shahid Beheshti University of Medical Sciences, Evin, Daneshjoo Blvd, P.O. Box 19615-1178, Tehran, IranTel + 98-21-22429768Fax + 98-21- 22432047Email s.asadi@sbmu.ac.ir Jamal ShamsBehavioral Research Center, Imam Hossain Educational Hospital, Shahid Beheshti University of Medical Sciences, Madani Ave, P.O. Box 1617763141, Tehran, IranTel/Fax + 98-21-77553074Email J_shams@sbmu.ac.irIntroduction: Studies have been reported that frequent use of methamphetamine (MA) is associated with brain function impairment, mood disorders and excessive free radical production accompanied by the decreased level of the antioxidant response elements, but no study investigated their correlations simultaneously. In the current study, the correlation of brain function, depression and anxiety levels, and the serum levels of PON1 (an antioxidant) in MA-dependent patients were investigated.Methods: Nineteen active MA abusers and 18 control subjects performed color-word Stroop task during fMRI and the state of their depression, anxiety, and stress were measured by the Depression, Anxiety and Stress Scale-21 Items (DASS-21) questionnaire. Their blood samples were collected to measure the level of PON1 by the human enzyme-linked immunosorbent assay (ELISA) kit and its correlation with the measured variables was studied.Results: Analysis of fMRI findings showed frontocingulate dysfunction in Stroop effect condition, including left anterior cingulate cortex, paracingulate gyrus, superior frontal gyrus, and frontal pole in MA-dependent patients, which was associated with a higher level of depression and decreased level of serum PON1 in these patients.Discussion: The results of the current study showed that MA-dependency is associated with frontocingulate dysfunction, decreased serum PON1 concentration, and increased depression/anxiety, which is worth to be more studied to elucidate their roles in the pathophysiology of MA addiction.Keywords: anxiety, depression, fMRI, PON1, Stroop task